Day 3 Wed, November 14, 2018 2018
DOI: 10.2118/193313-ms
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Testing of an Isolator Tool for High-Frequency Torsional Oscillation

Abstract: During downhole drilling, severe vibration loads can occur that affect the reliability and durability of tools in bottom-hole assemblies (BHA). These high-frequency torsional oscillations (HFTO) can cause premature damage to tools or their subcomponents. This paper presents dynamic simulations, prototype testing, and field test results of a BHA component that isolates the upper part of the BHA from HFTO. This isolation increases the performance and reliability of BHA components through reduction of the vibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Further investigation on detailed mechanical components in the BHA and geophysical/geomechanical parameter changes in lithology will be required. In fact, obtaining accurate Figure 30: e isolator tool comprised in a typical field BHA and its effect [75,76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation on detailed mechanical components in the BHA and geophysical/geomechanical parameter changes in lithology will be required. In fact, obtaining accurate Figure 30: e isolator tool comprised in a typical field BHA and its effect [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…Although HFTO can be measured and its effect is modeled and predicted, little can be done to mitigate HFTO while still maintaining efficient drilling, a string component with certain mass and stiffness properties could be used to isolate a portion of the BHA from HFTO. Based on restricting potential damaging HFTO vibrations to a part of the BHA that is designed strong enough to survive HFTO, tools for isolating HFTO from the lower to the upper part of the BHA have been developed by Heinisch et al [75] and Carpenter [76]. By using this isolator tool, the BHA is modified so that critical HFTO mode shapes only have significant amplitudes in the section below the isolator tool, preventing the propagation of higher-frequency torsional vibrations upward the BHA and string, as shown in Figure 30.…”
Section: Applications Based On High-frequency Measurementsmentioning
confidence: 99%
“…It has been shown that, for the torsional dynamic of the drill string, the energy input can be modeled using a nonlinear torque characteristic at the bit [8]. Due to improved and new measuring tools, high-frequency oscillations have been identified as the cause of numerous drill string failures and have been intensively investigated over the last years with studies [9,10], simulations [8,11] and experiments [12,13]. Especially drilling in hard and dense formations leads to highfrequency torsional oscillations (HFTO) with frequencies between 50 Hz and 500 Hz [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…As neither the parameters nor the design of the drill string can be changed arbitrarily, new downhole tools must be developed to reduce critical vibrations. An isolator tool based on the principle of mechanical low-pass filtering is analyzed in testing, simulation and operation [13] and reduces the amplitude in specific areas of the BHA. As the isolator does not mitigate the critical vibration along the entire drill string, further mitigation strategies are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Since the drilling parameters cannot be adjusted arbitrarily, further concepts have to be investigated. In downhole drilling systems, concepts based on isolation [14], energy transfer [15], and additional damping [12,13] have been discussed in the literature. Additional tools that are placed within the drill string have been investigated to reduce critical torsional vibration.…”
Section: Introductionmentioning
confidence: 99%